A Book on Economics for Sociological Reading - Troktsuk, Irina (Journal of Economic Sociology, 2023)
The book under review was first published in 2019 and could not help but draw attention from the academic community as a form of the intra- and interdisciplinary “self-reflection” for the two world “star” economists who received the Nobel Prize in 2019. Russian researchers had mixed reactions to the book, noting the development of tools to increase the efficiency of foreign aid to poor countries (see, e. g.: [Banerjee, Duflo 2007; 2009; Banerjee, Duflo, Glennerster, Kinnan 2015]); an issue topical in light of the number of the developing countries’ debts “forgotten” by the Russian state (see, e. g.: [Voronov 2020]). However, the book received positive reviews from both international and Russian readers. The former appreciated its accessible style, and the focus on applied solutions for the urgent socialeconomic global problems aimed at creating a more humane world. They, however, also, noted a lack of critical assessment of the ‘capitalist worldview’, ignorance of certain issues (for instance, shadow economy), overly bold comparisons and generalizations, and vague practical recommendations (see, e. g.: [Crabtree 2019; Ball 2020; Kumar 2020; Oommen 2020; Srivastava 2020]). Russian readers agreed with these remarks, but also noticed the regrettable mismatch between the scale and the regional coverage of the book, its reliance on facts and the fight against stereotypes, and the authors’ ignorance of the Russian “case” and political-economic generalizations, and also questioned the authors’ estimates and forecasts under and after the pandemic (see, e. g.: [Meshcheryakova 2020; Kushnarev 2021]). For the sociological reader interested in the current Russian realities, the review summarizes the main themes of the book as the status of economics and economy, types of social polarization, myths and facts about migration, opportunities and limitations of free trade, socialpsychological mechanisms of economic processes, uncertainty of economic growth, and ways to mitigate poverty. However, it is noted that it seems that one cannot speak of a victory over or even a tense struggle against poverty today due to the actualization of the militaristic-geopolitical agenda.